Mangrove Ecosystem Condition at Three Regency on The East Coast of North Sumatra: A Review - Bambang Hendra Siswoyo; Siti Mardiana; Raja Sabrina (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This study aims to analyze the condition of mangrove ecosystems in the three districts on the east coast of North Sumatra. Data collection was carried out from June to December 2023 in the Deli Serdang, Serdang Bedagai, and Langkat districts. The sampling location was determined by purposive sampling, and the target location was a mangrove area that had aquaculture activities. There were 9 sampling points, 3 points each in each district. Observations were made using a 10 x 10 m quadratic transect method with 20 replications. Density, relative density, frequency, relative frequency, dominance, and relative dominance were calculated to obtain the importance index value of each species. The calculation results showed that Rhizopohora apiculata with a density of 2359-4208 ind/ha with a relative density between 43.7-48.8%. The highest frequency and relative frequency values are also in R. apiculata, and R. mucronata species between 0.67 - 1 with a relative frequency between 25 - 44.4%. The highest species dominance and relative dominance of R.apiculata was 0.000010272 - 0.00001105, with a relative dominance of 23.07 - 40.25%. Therefore, these two species are the species with the highest importance index >65%.